Resilience to health shocks and the spatial extent of local labour markets: Evidence from the COVID-19 outbreak in Italy - Mattia Borsati; Michele Cascarano; Marco Percoco (Bocconi University, Centre for Research on Geography, Resources, Environment, Energy and Networks (GREEN), 2020)
SARS-CoV-2 uses human beings as means of transport. In addition to the general issue that fewer interpersonal contacts reduce the speed of contagion, less attention has been paid to the spatial configuration of such contacts. With respect to Italy, the virus severely affected the most industrialized area of the country, where the high density of economic activities also exhibits dense networks of commuting flows. In this article, we empirically investigate the relationship between the spatial extent of local labour markets, as defined by the structure of the commuting network, and the diffusion of COVID-19. To this end, we compute, for each municipality, the intensive and extensive margins of commuting flows and we measure the spread of the disease by considering excess mortality over the period of January-May 2020. By exploiting a rich and novel dataset, we find that the commuting network played a significant role in placing more connected places at more severe epidemiological risk. A back-of-the-envelope calculation suggests that if commuting patterns were 90% of the real ones, Italy would have suffered approximately 1 300 and 1 000 fewer fatalities in March and April, respectively.
Keywords: H12; I18; J61; R41; 330; COVID-19; Resilience; Local labour market; Commuting flows; Mobility